Program mengajar bahasa inggris dari rumah selama pandemi Covid 19 - Joko Prayudha. S (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
The covid 19 virus pandemic has stopped teaching and learning activities in schools and changed teaching methods to online teaching. This makes students feel bored because they cannot feel the learning atmosphere as usual. This activity provides an opportunity for students to be able to feel the learning atmosphere like in school by providing English teaching materials to students. In this activity, using a teaching method and through a socialization and training approach to students by providing understanding and explanation of English learning material in a fun way. This activity was carried out for one full month to provide a forum for teaching English to students affected by the COVID-19 pandemic. It is hoped that in this activity students are able to understand English learning material well and can experience learning again together with their classmates even though they have to follow protocols. health.